Development of the Android-Based Learning Application ELEN (Enjoy Learning English) to Improve Students’ Learning Outcomes in English Vocabulary for Grade V - Istiqomah, Laili; Inayati, Denik Rohmah (Mentari : Journal of Islamic Primary School, 2024)
Technological advancements require the education sector to adapt continuously, including in the development of learning media. Smartphone-based Android applications owned by students can be utilized as a medium for developing learning resources. The limited use of Android applications as learning media forms the background of this study. In addition, limited instructional time and students’ low interest in reading books make the development of Android-based learning media highly relevant. Therefore, the researcher conducted a research and development study to develop an Android-based learning application for English vocabulary for Grade V students at SD IT Al-Furqon. This study aims to examine: (1) the development of an Android-based learning application for English vocabulary for Grade V students at SD IT Al-Furqon Karangtengah Garu, Baron, Nganjuk in the 2023/2024 academic year; (2) the validation of the Android-based learning application for English vocabulary for Grade V students; and (3) the effectiveness of the Android-based learning application in improving students’ English vocabulary learning outcomes. This research employed a Research and Development (R&D) approach. The development model used in this study refers to the 4-D model proposed by Thiagarajan, which consists of four stages: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. Data collection instruments included validation questionnaires administered to media experts and subject-matter experts, as well as pre-test and post-test instruments given to students to measure the effectiveness of the developed product. Quantitative data analysis was used to assess the validity and effectiveness of the product. The result of this research and development is an Android application named ELEN (Enjoy Learning English), which features learning materials, instructional videos, and quizzes. Product validation by media and material experts obtained an overall average percentage score of 98%, indicating that the product is valid. Furthermore, the calculation of the N-gain score from the pre-test and post-test results yielded a value of 0.81 or 81.5%, indicating that the developed product falls into the “high” score category and demonstrates an “effective” level of effectiveness.